Genetic analysis and QTL detection of reproductive period and post-flowering photoperiod responses in soybean - Cheng, Lirui; Wang, Ying; Zhang, Chunbin; Wu, Cunxiang; Xu, Jianlong; Zhu, Huiying; Leng, Jiantian; Bai, Yangnian; Guan, Rongxia; Hou, Wensheng; Zhang, Lijuan; Han, Tianfu (Theoretical and applied genetics, 2011)
Reproductive period (RP) is an important trait of soybean [ Glycine max (L.) Merr.] It is closely related to yield, quality and tolerances to environmental stresses. To investigate the inheritance and photoperiod response of RP in soybean, the F 1 , F 2 , and F 2:3 populations derived from nine crosses were developed. The inheritance of RP was analyzed through the joint segregation analysis. It was shown that the RP was controlled by one major gene plus polygenes. 181 recombinant inbred lines (RILs) generated from the cross of Xuyong Hongdou × Baohexuan 3 were further used for QTL mapping of RP under normal conditions across 3 environments, using 127 SSR markers. Four QTLs, designated qRP-c-1 , qRP-g-1 , qRP-m-1 and qRP-m-2 , were mapped on C1, G and M linkage groups, respectively. The QTL qRP-c-1 on the linkage group C1 showed stable effect across environments and explained 25.6, 27.5 and 21.4% of the phenotypic variance in Nanjing 2002, Beijing 2003 and Beijing 2004, respectively. Under photoperiod-controlled conditions, qRP-c-1 , and two different QTLs designated qRP-l-1 and qRP-o-1 , respectively, were mapped on the linkage groups L and O. qRP-o-1 was detected under SD condition and can explained 10.70% of the phenotypic variance. qRP-c-1 and qRP-l-1 were detected under LD condition and for photoperiod sensitivity. The two major-effect QTLs can explain 19.03 and 19.00% of the phenotypic variance, respectively, under LD condition and 16.25 and 14.12%, respectively, for photoperiod sensitivity. Comparative mapping suggested that the two major-effect QTLs, qRP-c-1 and qRP-l-1 , might associate with E8 or GmCRY1a and the maturity gene E3 or GmPhyA3, respectively. These results could facilitate our understanding of the inheritance of RP and provide information on marker-assisted breeding for high yield and wide adaptation in soybean.